Portrait of Islamic Economic Literacy on Students of Department Sharia Economics IAIN Kerinci - Bustami, Alek Wissalam; Fauzi, Muhammad (Jurnal Iqtisaduna, 2023)
This study aims to investigate the level of Islalmic Economic Literacy (IEL) among students of the Department of Sharia Economics (DSE) Institut Agama Islam Negeri Kerinci (IAIN Kerinci). Investigation IEL levels in terms knowledge, understanding, and ability to apply attitudes (actions) from Islamic economics material that has been stuDSEd into everyday life. The research data comes from primary data collected using the Miles and Huberman model as a qualitative data analysis tool. This study shows that the level of IEL among students DSE IAIN Kerinci is in the pretty good category. This is evidenced by the fact that there are still many students who lack knowledge and understanding of Islamic economics material. Even though academic achievement or Grade Point Average (GPA) is above 3.50. It was even found that a higher GPA still lacks knowledge and understanding compared to a low GPA. Even though knowledge and understanding are still very minimal, the ability to apply attitudes (behavior) in daily economic activities has been applied in accordance with Islamic economics. This study can be the target of related parties to focus their full attention on increasing IEL in students DSE IAIN Kerinci. This study can also contribute to the reading of Islamic economics literature and the study of IEL, and at the same time, it opens up the door for further research.